Applying Item Response Theory Analysis to the Montreal Cognitive Assessment in a Low-Education Older Population. (October 2020) - Luo, Hao; Andersson, Björn; Tang, Jennifer Y. M.; Wong, Gloria H. Y.
The traditional application of the Montreal Cognitive Assessment uses total scores in defining cognitive impairment levels, without considering variations in item properties across populations. Item response theory (IRT) analysis provides a potential solution to minimize the effect of important confounding factors such as education. This research applies IRT to investigate the characteristics of Montreal Cognitive Assessment items in a randomly selected, culturally homogeneous sample of 1, 873 older persons with diverse educational backgrounds. Any formal education was used as a grouping variable to estimate multiple-group IRT models. Results showed that item characteristics differed between people with and without formal education. Item functioning of the Cube, Clock Number, and Clock Hand items was superior in people without formal education. This analysis provided evidence that item properties vary with education, calling for more sophisticated modelling based on IRT to incorporate the effect of education.